Design and Implementation of an Arduino Uno-Based RPM Control System for a Treadmill - Ana Uzla BatuBara; Berkat Panjaitan; Agusto Feliks Simanjuntak (CV. AFDIFAL MAJU BERKAH, 2025)
This research presents the design and development of an RPM (Revolutions Per Minute) controller for a treadmill using Arduino UNO. The treadmill is a medical device commonly used to evaluate cardiac performance under increasing levels of physical activity. Its primary function is to monitor how the heart responds to progressively intense exercise. In this design, the treadmill is powered by an AC motor, with RPM speed regulated through a timer and driven by a servo motor programmed via Arduino UNO. The system is designed to display RPM values of 550, 750, 950, and 1100 on the interface. This development aims to support more accurate and controlled cardiac stress testing through precise speed adjustments.